A bile‐salt derived porous hierarchical MnO2 nanoflowers as electrodes for symmetric supercapacitors. Issue 4 (17th August 2021) - Kumar, Ajay; Dillip, Gowra Raghupathy; Bharti, Abhishek; Maitra, Uday; Bhattacharyya, Aninda J.
Abstract: We demonstrate here a porous hierarchical nanostructured MnO2 as electrodes for supercapacitors. The synthesis of MnO2 nanostructure uses a bile salt viz. sodium‐7‐deoxycholate, which acts as both a reducing and structure‐directing agent. The radially grown MnO2 nanoflowers self‐assemble to form hierarchical nanostructures. The MnO2 samples synthesized at higher reaction temperatures resulted in a higher surface area. Depending on the reaction temperature, the surface area of this unique morphology is as high as 222 m 2 /g. The MnO2 synthesized at elevated temperatures display a higher specific capacitance (=144.1 F/g @ 0.1 A/g) in comparison to both the room temperature synthesized MnO2 (122.7 F/g @ 0.1 A/g) and commercial MnO2 (25.3 F/g at 0.1 A/g). The differences in the electrochemical performance between various samples are due to varying impurities such as sodium and potassium ions present in the samples. Symmetric supercapacitor cells of proposed MnO2 exhibits higher specific capacitance of 63.6 F/g and higher specific energy of 7.9 Wh/kg at a current density of 1 A/g. The MnO2 nanostructures show outstanding cyclic stability with the excellent capacitance retention of about 97% of its initial value after 2000 cycles. Abstract : Highly porous MnO2 nanoflowers and their Na/K ions contents dependent electrochemical properties for symmetric supercapacitors